Prevalence of Hypertension and Diabetes Mellitus in Patients Thrombolysed for STEMI - Zia Ullah Khan, Wasif Ullah, Saad Shams, Sania Saleem, Rukhshanda Afsar, Sana Ullah Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study is to evaluate the frequency of hypertension and diabetes in patients, thrombolysed for STEMI and explore the relationship between these comorbidities and patient outcomes. By examining the frequency of these comorbidities in thrombolysed STEMI patients, healthcare providers can develop personalized treatment plans to optimize patient outcomes. Furthermore, these findings have the potential to contribute to future research focused on preventing or managing hypertension and diabetes in STEMI patients. Study Design: cross sectional study Study Setting: Cardiology Department, Ayub Teaching Hospital, Abbottabad, Pakistan. Duration of Study: Six months from August 1st, 2022 to 31st Jan, 2023. Material and Methods:. A total of 170 patients, aged between 18 and 80 years, were included in the sample for analysis. The study focused specifically on patients who were thrombolysed using Streptokinase. Results: In this study, male to female ratio was nearly 3:1. Among the 170 patients, 96 (56%) were found to have hypertension, while 42 (24%) were diagnosed with diabetes. Among the hypertensive patients, which accounted for 96 (56%) of the total population, 60 (62.5%) were male and 36 (37.5%) were female. Among these diabetic patients, 24 (57.1%) were male, while 18 (42.9%) were female. Conclusion: This study highlights the high frequency of hypertension and diabetes in ST-elevation myocardial infarction (STEMI) patients treated with thrombolytic therapy. These findings suggest the importance of screening STEMI patients for these comorbidities and providing appropriate follow-up care to optimize patient outcomes. Keywords: Prevalence, Hypertension, Diabetes, STEMI.